1987
DOI: 10.1002/ccd.1810130411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of superflow (5F) and conventional 8F catheter for cardiac catheterization by the femoral route

Abstract: In order to determine whether the use of a smaller catheter would allow day-case cardiac catheterization by the femoral route, the performance of the Superflow (5F) and the 8F catheters was compared in 34 adults who underwent left ventriculography and coronary angiography. As shown by the significantly lower fluoroscopy time [2.8 +/- 1.2 min vs 4.5 +/- 2.7 min, (m +/- SD), p = 0.027] the 8F catheter was more maneuverable than the Superflow (5F) catheter. Poor left ventriculograms were obtained in a higher prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In order to reduce these and improve patient comfort, efforts have been made to reduce progressively the size of cardiac catheters. Earlier studies [5][6][7]12] with 4 and 5 Fr catheters found angiographic quality to be reduced and noted technical problems relating to contrast injection and catheter displacement from the coronary ostia during injection. A study of 4 Fr catheters used from the brachial route [13] also found angiographic quality to be inferior with 4 Fr catheters, with the most marked differences noted in opacification of the LAD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to reduce these and improve patient comfort, efforts have been made to reduce progressively the size of cardiac catheters. Earlier studies [5][6][7]12] with 4 and 5 Fr catheters found angiographic quality to be reduced and noted technical problems relating to contrast injection and catheter displacement from the coronary ostia during injection. A study of 4 Fr catheters used from the brachial route [13] also found angiographic quality to be inferior with 4 Fr catheters, with the most marked differences noted in opacification of the LAD.…”
Section: Discussionmentioning
confidence: 96%
“…Local vascular complications remain the most frequent complication of coronary angiography (0.43%-0.6% of cases) [3] and are more common with larger-size femoral punctures [4]. Early work [5][6][7] with smaller diameter catheters was not encouraging. Despite achieving ambulation at a mean of 2.6 hr, the operators criticized catheter handling and the quality of angiographic images obtained [8].…”
Section: Introductionmentioning
confidence: 96%
“…If similar results could be obtained with smaller 5 or 6 French catheters, patient acceptance of the follow-up catheterization required for coronary artery disease intervention studies could be optimized. Limited data suggest that this may not be possible with 5 French catheters [11][12][13][14]. In this study, 20 mild to moderately severe stenoses from 15 patients enrolled prospectively were sequentially interrogated using standard 8 French catheter techniques and 6 French catheters using hand and power injection, and cine acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…This was looked at by Molajo et al [7], who compared the performance of the 8F catheter and the new "superflow" 5F (Cordis) catheter, which has a larger luminal diameter than the normal 5F. They observed that, although there was no significant difference in the bleeding complications between the two catheters, the fluoroscopic time was significantly more with the 5F and this was also associated with poor torque and general image quality.…”
Section: Discussionmentioning
confidence: 93%